Formulation, Characterisation and Preclinical evaluation of Antidiabetic activity of Polyherbal tablet - B Ray; B B Panda; P K Biswal (International Journal of Phytomedicine, 2021)
Diabetes mellitus is a complex and a diverse group of disorders that disturbs the metabolism of carbohydrate, fat and protein. The number of diabetes mellitus cases has been increasing worldwide in recent years. In 2000, the WHO estimated a total of 171 million people with diabetes mellitus from the global population, and this report projected to increase to 366 million by 2030. Now a days polyherbal formulations made by a different herbal pharmaceutical company is very much popular and acceptable for chronic use in case of diabetes, hypertension, bronchial asthma, hyperlipidemia, rheumatoid arthritis, etc. As the incidence of diabetes is increasing day by day globally, and the rate of occurrence of disease in India is tho high, the popularity of polyherbal formulation is increasing day by day. many physicians from a different system of medicine refer to advice polyherbal formulations for long time use in patient of diabetes, as the manufacturer of herbal formulator claim the formulation is having a negligible side effect. Present Study was delt with Evaluation of antihyperglycemic Potential of prepared polyherbal Formulation PHF i.e. with 1mg/kg and 1.5 mg/kg, the FBS level was reduced from 187.16 ± 3.25 to 133.16 ± 2.93 and 181.5 ± 4.42 to 136.33 ± 2.58, respectively. In the combination regimen of PHF (1.5mg/kg) and Metformin (50mg/kg) the mean FBS level dropped from 180.3 ± 1.75 to 131.16 ± 2.14. In all these groups the mean FBS level has reached the normal pre-induction level. The daily single administration of PHFformulation(1.5mg/kg) and Metformin (50 mg/kg) significantly reduced blood sugar levels of Streptozotocin (STZ) induced diabetic mice. It also important to study antihyperglycemic effect of the said Polyhedral Formulation in Different animal Model to conclude exact pattern of Anti hyperglycaemic activity.